Fonsecaea pedrosoi Sclerotic Cells: Secretion of Aspartic-Type Peptidase and Susceptibility to Peptidase Inhibitors - Palmeira, Vanila F.; Goulart, Fatima R. V.; Granato, Marcela Q.; Alviano, Daniela S.; Alviano, Celuta S.; Kneipp, Lucimar F.; Santos, André L. S. (Frontiers in Microbiology, 2018)
Fonsecaea pedrosoi is a dematiaceous fungus and the main causative agent of chromoblastomycosis that is a chronic disease usually affecting the human skin and subcutaneous tissues, which causes deformations and incapacities, being frequently refractory to available therapies. A typical globe-shaped, multiseptated and pigmented cells, known as sclerotic bodies, are found in the lesions of infected individuals. In the present work, we have investigated the production of aspartic-type peptidase in F. pedrosoi sclerotic cells as well as the effect of peptidase inhibitors (PIs) on its enzymatic activity and viability. Our data showed that sclerotic cells are able to secrete pepstatin A-sensible aspartic peptidase when grown under chemically defined conditions. In addition, aspartic PIs (ritonavir, nelfinavir, indinavir and saquinavir), clinically used in the HIV chemotherapy, significantly decreased the fungal peptidase activity, varying from 55 to 99%. Moreover, sclerotic cell-derived aspartic peptidase hydrolyzed human albumin, an important serum protein, as well as laminin, an extracellular matrix component, but not immunoglobulin G and fibronectin. It is well-known that aspartic peptidases play important physiological roles in fungal cells. With this task in mind, the effect of pepstatin A, a classical aspartic peptidase inhibitor, on F. pedrosoi proliferation was tested. Pepstatin A inhibited the fungal viability in both cellular density- and drug-concentration manners. Moreover, HIV-PIs at 10 µM powerfully inhibited the viability (>65%) of F. pedrosoi sclerotic cells. The detection of aspartic peptidase produced by sclerotic cells, the parasitic form of F. pedrosoi, may contribute to reveal new virulence markers and potential targets for chromoblastomycosis therapy.